Radioactive waste from nuclear power plants stays radioactive and deadly for hundreds oh thousands of years : We can generate electricity in safer ways - Young, Daniel ([s. n.], 2013)
Na žutoj podlozi, u središtu plakata, točkastim rasterom oblikovana atomska jezgra čiji je središnji dio nalik mrtvačkoj glavi